Spaces:
Running
on
CPU Upgrade
DeepSeek V3 Sovling recurrence
๐: if S(2^(n+1)) = 2*S(2^n) + 2^n for n=1,2,3,4 ...
and S(2) =1
find a general value for S(2^n)
๐ค: We are given the recurrence relation:
[
S(2^{n+1}) = 2 \cdot S(2^n) + 2^n
]
with the initial condition ( S(2) = 1 ). We want to find a general expression for ( S(2^n) ).
Step 1: Rewrite the recurrence
Let ( a_n = S(2^n) ). Then the recurrence becomes:
[
a_{n+1} = 2a_n + 2^n
]
with the initial condition ( a_1 = 1 ).
Step 2: Solve the recurrence
This is a linear nonhomogeneous recurrence relation. We first solve the homogeneous part:
[
a_{n+1}^{(h)} = 2a_n^{(h)}
]
The solution to this is:
[
a_n^{(h)} = C \cdot 2^n
]
Next, we find a particular solution to the nonhomogeneous recurrence. We guess a solution of the form ( a_n^{(p)} = A \cdot n \cdot 2^n ). Substituting into the recurrence:
[
A \cdot (n+1) \cdot 2^{n+1} = 2 \cdot A \cdot n \cdot 2^n + 2^n
]
Simplify:
[
2A(n+1)2^n = 2An2^n + 2^n
]
Divide both sides by ( 2^n ):
[
2A(n+1) = 2An + 1
]
Simplify:
[
2An + 2A = 2An + 1
]
This gives:
[
2A = 1 \implies A = \frac{1}{2}
]
Thus, the particular solution is:
[
a_n^{(p)} = \frac{1}{2} \cdot n \cdot 2^n = n \cdot 2^{n-1}
]
The general solution is the sum of the homogeneous and particular solutions:
[
a_n = C \cdot 2^n + n \cdot 2^{n-1}
]
Step 3: Apply the initial condition
Using ( a_1 = 1 ):
[
1 = C \cdot 2^1 + 1 \cdot 2^{0} = 2C + 1
]
Solving for ( C ):
[
2C = 0 \implies C = 0
]
Thus, the solution is:
[
a_n = n \cdot 2^{n-1}
]
Step 4: Write the final expression
Since ( a_n = S(2^n) ), we have:
[
S(2^n) = n \cdot 2^{n-1}
]
Verification
For ( n = 1 ):
[
S(2^1) = 1 \cdot 2^{0} = 1
]
For ( n = 2 ):
[
S(2^2) = 2 \cdot 2^{1} = 4
]
For ( n = 3 ):
[
S(2^3) = 3 \cdot 2^{2} = 12
]
These values satisfy the recurrence relation, confirming the solution.
Final Answer
[
S(2^n) = n \cdot 2^{n-1}
]